Comparative assessment of European tools to estimate traffic emissions - Zachariadis, Theodoros; Samaras, Zissis (My University, 1997)
Four models used to calculate motor vehicle emissions across Europe (Handbook of Emission Factors, Drive-Modem model, Digitalized Graz Method and Computer Programme to Calculate Emissions from Road Traffic) are compared. The focus is on their methods for the estimation of emissions of passenger cars. By using driving profile data from real-world recordings in urban streets as well as general emission functions, the results obtained from the four models are presented and discussed. Furthermore, on the basis of relevant investigations conducted in Europe, including this one, a number of critical vehicle emission modelling issues are discussed: (i) whether detailed methodologies lead indeed to improved emission estimates, (ii) how refined vehicle emission models have to be for use in different applications, and (iii) if it is possible to have one method and model for estimating vehicle emissions in any type of application.
Keywords: Emission inventories; Emissions; Models; Road traffic; Vehicles